2010
DOI: 10.1186/1477-7525-8-83
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the Eating Disorders Quality of Life Scale (EDQLS) in a longitudinal multi-site sample

Abstract: BackgroundIn eating disorders (EDs), treatment outcome measurement has traditionally focused on symptom reduction rather than functioning or quality of life (QoL). The Eating Disorders Quality of Life Scale (EDQLS) was recently developed to allow for measurement of broader outcomes. We examined responsiveness of the EDQLS in a longitudinal multi-site study.MethodsThe EDQLS and comparator generic QoL scales were collected in person at baseline, and 3 and 6 months from 130 participants (mean age 25.6 years; rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
(57 reference statements)
1
16
0
Order By: Relevance
“…For the ITT sample, outcomes were attenuated but nonetheless substantial (~62% ED psychopathology,~63% QOL). The improvement in QOL is consistent with other findings (Adair et al, 2007;Adair, 2008;de la Rie et al, 2005;Halvorsen & Heyerdahl, 2006;Las Hayas et al, 2007;McHugh, 2007;Padierna et al, 2002). The results reflect those possible in naturalistic settings, unlike investigations in 'laboratory-based' contexts, which generate data on optimal outcome under ideal conditions (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For the ITT sample, outcomes were attenuated but nonetheless substantial (~62% ED psychopathology,~63% QOL). The improvement in QOL is consistent with other findings (Adair et al, 2007;Adair, 2008;de la Rie et al, 2005;Halvorsen & Heyerdahl, 2006;Las Hayas et al, 2007;McHugh, 2007;Padierna et al, 2002). The results reflect those possible in naturalistic settings, unlike investigations in 'laboratory-based' contexts, which generate data on optimal outcome under ideal conditions (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Although there is a sparsity of research, initial findings suggest that QOL may improve with ED treatment; however, may not return to community normative levels (e.g. Abraham et al, 2006;Adair, 2008;de la Rie, Noordenbos, & van Furth, 2005;Halvorsen & Heyerdahl, 2006;Las Hayas et al, 2007;Padierna et al, 2000Padierna et al, , 2002Pohjolainen et al, 2010). Additionally, few studies have considered QOL outcomes associated with specific treatment modalities or the factors associated with higher post-treatment QOL.…”
mentioning
confidence: 99%
“…A comparison of the matched and unmatched mentees revealed that matched mentees reported significantly higher levels of quality of life in the education/vocation, family and close relationships, future outlook, psychological, emotional, values and beliefs, and physical domains than unmatched mentees. It is important to note that mentors’ scores on the EDQLS are consistent with individuals who report low eating disorder symptoms and high levels of functioning [ 32 ]. In contrast, both matched and unmatched mentees are reporting quality of life levels consistent with those with high eating disorder symptoms and overall psychiatric symptom severity [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the last few years the trend is changing and nowadays most of the investigations include quality of life measures. It is important to remark that recently some instruments have been developed to assess quality of life in ED patients like the Health-Related Quality of Life in Eating Disorders (HeRQoLED; Las Hayas et al, 2006), the Quality of Life for Eating Disorders questionnaire (QOL ED-H; Abraham, 2008;Abraham et al, 2006), the Health Related Quality of Life for the Eating Disorders (HeRQoLED-S; Bamford, 2010) and the Eating Disorders Quality of Life Scale (EDQLS; Adair et al, 2010) that are used with clinical samples but that do not include hedonic and eudaimonic components of well-being. Quality of life measures in ED have become more popular and most of the researchers recognize the importance of evaluating well being and functioning in specific domains of life that may be affected by ED (Bamford & Sly, 2010).…”
Section: Discussionmentioning
confidence: 99%